The Malay’s Traditional Delicacy: The Practice of Bubur Anak Lebah in Perak - Apriyanto, Yusup; Muhammad Idrus, Muhammad Haikhal Afiki (Politeknik Pariwisata Lombok, 2024)
Introduction: This paper qualitatively explores the significance of Bubur Anak Lebah including the preparation, cooking methods, food decorum, and its practice in the current day. Methodology: The study informants are people who understand the practices of Bubur Anak Lebah from the past times until recent days who live in Ipoh, Perak. Data was collected through field observations and analyzed using narrative methods. Findings: This study found that Bubur Anak Lebah is a traditional Malaysian dish made from rice flour, tapioca flour, and pandan leaf. It is prepared through three steps: mixing the ingredients, boiling the liquid, and pressing the dough. The dish is served warm or hot, with a chewier texture similar to cendol. It can be colored brownish, green, or pale, depending on the sugar type. Historically, it was eaten by mothers after abstinence and Majelis Cukur jambul for babies and today it is served during Ramadhan bazaars or family times. Conclusion: This study highlights that there are some different practices in using ingredients, cooking methods, and usage of Bubur Anak Lebah in local events in the past and recent days. Keywords: Heritage, Malay, Traditional, Food, Bubur